PENGARUH PERUBAHAN MEREK DAN KEPUASAAN KONSUMEN TERHADAP LOYALITAS PELANGGAN PADA FIFGROUP - Hermawan, Elpa (Perspektif : Jurnal Ekonomi dan Manajemen Akademi Bina Sarana Informatika, 2019)
The aims of research is to find out the effect of brand changes and consumer satisfaction on consumer loyality at FIFGROUP. The research method used descriptive quantitative survey and data collection technique used area sampling techniques with the number of respondents were 150 people,. The technique of data analysis is multiple linear regression equation. The results of research showed that customers understand the changes of brand and logo of the company, but the results of the calculations show that there is no influence of the change of brand and customer satisfaction to customer loyalty. In conducting this recearch, the researchers was faced by some constraints, especially constraints to obtain data on the number of customer’s detail , as well as data concerning the company's consideration in making the change of brand and logo, so further research is effective to do.